Role of mentoring in career adaptability and ambiguity tolerance of potential Nigerian entrepreneurs: The moderating effect of age - Omonigho Simon Umukoro; David Efevogho Okurame (Journal of Global Entrepreneurship Research, 2018)
This study examines age differentials in the predictive role of entrepreneurial mentoring on career adaptability and ambiguity tolerance among potential Nigerian entrepreneurs. A cross-sectional survey was adopted in obtaining relevant data for the study. The study participants were graduates who were participating in the National Youth Service Corp (NYSC) in Nigeria. This population forms a catchment group for entrepreneurship programmes in Nigeria. Their ages ranged from 19 to 30 years old; with 780 being male and 846 being female. Results showed that the interaction term of age and mentoring produced significant effect (B = .174; p < .05) and accounted for a significant increase in career adaptability (ΔR2 = 0.4%; p < .05). The results imply that the effects of entrepreneurial mentoring on career adaptability were significant among both younger and older graduates; with a stronger effect being observed among the former (B = .23, CI = .09 to .17) than the latter (B = .01, CI = .17 to .24). However, age did not moderate the effect of mentoring on ambiguity tolerance (B = .033; p > .05). These results buttress appeals for incorporating adaptive mentorship models that cater for contextual factors (such as age differences) in entrepreneurship education aimed at enhancing specific modules of career adaptability and other important entrepreneurial traits.
Keywords: 650; Entrepreneurship; Mentoring; Career adaptability; Ambiguity tolerance; Age; Graduates